Gestão da formação em contexto: processos de criação da documentação pedagógica formativa - Menezes, Juliana Pinto Gomes de (2024)
This study is linked to the Professional Master's Degree of the Postgraduate Program in Public Policies and Educational Management at the Federal University of Santa Maria (UFSM) in research line 2 - Pedagogical Management and Educational Contexts, and its main objective is to understand whether the proposal for managing training in context, experienced by the teaching collective that lives at CEI Casa da Criança, makes it possible to experience processes of collaborative pedagogical practices. This research arises with the physical, structural and pedagogical reform of CEI Casa da Criança, in addition to the expansion of the headquarters structure and the creation of the Unit, bringing the need to form a teaching collective to think and act in the (re)construction of the school's identity, with collaborative proposals. This research was developed through a qualitative approach, being considered applied in nature and implied by being linked to the researcher's work context. Built from the perspective of action research, covering the idea of craftsmanship. The teaching collective that lives in the school is considered subjects. The strategies used in the research were: training meetings, which consist of pedagogical meetings, collaborative planning meetings and day-to-day movements; and formative records documented in two ways, individually and collectively.To record the processes followed by the proposed strategies, three instruments were used: the researcher's record in the form of a notebook of what was experienced, the teachers' individual record, called a booklet, and the collective record made from the systematization of the training meetings. These movements generated three main lines that ran throughout the development of the research: training in context, documentation of the processes of construction of practices, and the crossings of context management. These lines organized the dialogue between the processes and contributed to reflection, understanding, resistance and possibilities for transforming what is experienced individually and collectively. However, it was noticed that we have not reached the end of the journey, as this training path continues, with new experiences and trajectories that will contribute to the pedagogical proposal, but, as a result of this training process in context, the elaboration of a Formative Pedagogical Documentation is presented, making it possible to document practices and reflections, thus teachers construct their professional identity and as a group, strengthening the recognition of their reflective and transformative role, giving visibility to their constructions and (re)constructions of meanings based on relationships between theory and practice, creating a professional role that enriches and qualifies work in the school context and demonstrates the importance of building meaningful and participatory pedagogical practices.